Analisis Lalu Lintas Terhadap Kapasitas Jalan di Kota Tegal (Studi Kasus Simpang Kejambon Tegal) - Isradias Mirajhusnita (Universitas Pancasakti Tegal, 2019)
Problems in transportation, especially land transportation is one of the things that are difficult to solve, the problems that often occur is the density of the traffic. The growth and development of today's population is increasingly difficult to control, resulting in increasing human activities and complex, this problem arises due to the growth of transportation with unbalanced road infrastructure, where Means of transportation in the present era continues to grow larger. Then there will arise various traffic problems, which include prolonged congestion. In this research, the location chosen as the location of the study is the intersection of Kejambon Street, Tegal. The selection of these research locations because certain hours often occur long queues so it is possible to do a study. Result of research by Manual method of road capacity Indonesia (MKJI) 1997. Based on the calculation result of the field data can be known that the capacity of Kejambon Intersection, Tegal City. At the north of the degree of saturation (DS) = 0.922, the western close to the degree of saturation (DS) = 0.886, the south-close degree of saturation (DS) = 0.928 and the east close to the degree of saturation (DS) = 0.934. This indicates that the Kejambon Intersection, Tegal City, is approaching through saturation, which will cause a long queue in peak traffic conditions. Delay intersectionaverage in the junction of Kejambon, Tegal City obtained 86 sec/smp, which means that the junction of Kejambon, Tegal City, including in the service level F, showed the level of service of the worst in peak traffic conditions.